With malice toward all? : the media and public confidence in democratic institutions - Moy, Patricia (Praeger series in political communication., 2000)
Public opinion polls point to a continuing decline of confidence in the Presidency, court system, Congress, the news media, state government, public education, and other key institutions. Moy and Pfau examine the role of the media in the decline of the American public's confidence in democratic institutions.